Control of underactuated marine crafts with matched disturbances. Issue 6 (3rd June 2022) - Kennedy, Justin M.; Donaire, Alejandro; Ford, Jason J.
ABSTRACT: Stabilisation of marine craft in the presence of disturbances is important to many offshore activities. The process of stabilising a marine craft using the actuators is known as dynamic positioning, and is challenging for underactuated craft. In our work, we develop a robust dynamic positioning controller for an underactuated marine craft that ensures input-to-state-stability with respect to matched disturbances. Using the strict Lyapunov function approach of Malisoff and Mazenc [(2009). Constructions of strict Lyapunov functions . Springer-Verlag], we show that the proposed controller ensures uniform global asymptotic stability of the desired equilibrium when there are no disturbances. We also show that the closed-loop system is input-to-state stable with respect to matched environmental force and moment disturbances. Finally, we illustrate the performance of the proposed controller through simulations.